High-strength steel laser welding filler, joint and method
By controlling the range of alloy components in high-strength steel laser welding fillers, stabilizing the austenite structure and evenly distributing the alloy components, the problem of degradation of the strength and toughness of the hot-formed high-strength steel welded joints is solved, and the high strength and toughness of the welded joints are achieved, reaching more than 90% of the performance of the base material.
Patent Information
- Application Number
- CN202211262308.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-14
AI Technical Summary
During the welding process of thermoformed high-strength steel, the aluminum elements in the aluminum-based coating are prone to invade the welding structure, forming brittle phase and ferrite structure, resulting in a decrease in the strength and toughness of the welded joints, affecting the joint performance.
A high-strength steel laser welding filler is used, and its components include Fe as a substrate, 0.05%-0.5% C, 0.1%-2% Cu, 0.2%-2.5% Cr, 0.5%-3.5% Mo, 2%-10% Ni, and inevitable impurities. By controlling the range of alloy components, the austenite structure is stabilized, the formation of ferrite is inhibited, and the alloy components are evenly distributed in the weld structure to improve the weld strength.
By using this welding filler, the strength and plasticity of the welded joints reach more than 90% of the property of the base material after hot stamping, which significantly improves the strength and toughness of the joints and meets the application needs of high-strength structural materials.
Smart Images

Figure CN115446459B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of laser welding, and in particular relates to a high-strength steel laser welding filler, a joint and a method. Background Art
[0002] Hot-formed high-strength steel is a commonly used structural material in automobile manufacturing. It usually has a high strength of more than 1500MPa and is suitable for the processing and manufacturing of important structural parts such as A-pillars and main longitudinal beams. The hot forming process of hot-formed high-strength steel usually requires heating the workpiece to 880-950℃, keeping it warm for 3-6 minutes (the heating temperature and holding time vary depending on the size and thickness of the workpiece), and then quenching. In this process, in order to avoid oxidation of the steel surface at high temperatures, it is usually necessary to apply an aluminum-based coating to isolate the steel from the air, such as aluminum-silicon coated hot-formed steel. During the welding process, the aluminum element in the coating can easily invade the welding structure, forming a brittle phase and ferrite structure, affecting the joint performance.
[0003] In order to solve this problem, in actual production, it is usually necessary to pre-grind the welding area of hot-formed high-strength steel to remove the aluminum-based coating, which brings additional processing costs; or use materials containing high proportions of Mn, Cr, Ni and other alloy components as fillers to inhibit the formation of Al-containing brittle phases, but the negative effects such as segregation caused by excessive alloy components will also cause the mechanical properties of the joint to decline. These unfavorable factors restrict the application of hot-formed high-strength steel. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength steel laser welding filler to improve the strength and toughness of a high-strength steel laser welded joint with an aluminum coating. The present invention also provides a high-strength steel laser welded joint and a welding method.
[0005] According to an embodiment of one aspect of the present invention, a high-strength steel laser welding filler is provided, which takes Fe as a base material and comprises, by weight, 0.05%-0.5% C, 0.1%-2% Cu, 0.2%-2.5% Cr, 0.5%-3.5% Mo, 2%-10% Ni, and inevitable impurities.
[0006] Al is a ferrite stabilizing element, which can easily lead to low-hardness ferrite remaining in the weld solidification structure; at the same time, the Al element itself is prone to aggregation and forms brittle intermetallic compounds in the weld structure. These factors together lead to the decline in the strength of the welded joints of high-strength steel with pure aluminum or aluminum-based coatings. Existing welding fillers usually use the filler itself to dilute the Al element entering the weld to reduce the negative impact of the Al element on the joint strength, but the effect is limited. Under some working conditions, the strength and plasticity of the welded joint obtained are even less than 70% of the parent material. After a lot of research and experiments, the inventor controlled the alloy composition in the welding filler within a reasonable range. On the one hand, it can effectively stabilize the austenite structure and inhibit the formation of ferrite during the solidification process. On the other hand, the alloy components in the filler can be evenly distributed in the weld structure to achieve the effect of improving the weld strength. The strength and plasticity of the joint finally obtained after hot stamping reach more than 90% of the performance of the parent material after hot stamping.
[0007] Furthermore, the welding filler also includes 1.0%-5.0% Mn and 0.5%-3.0% Si. When the C content of the weld is too high, it will cause hardening of the structure, cracks, and reduce the toughness of the joint. Adding Mn elements can partially replace the role of C and reduce the C content in the filler; Si can improve the fluidity of the filler during the filling process and promote the uniform distribution of the filler.
[0008] Furthermore, the welding filler also includes 0.1%-1% Ti. The addition of Ti helps to refine the weld structure, solidify part of the C element and play a pinning operation, further improving the strength and toughness of the joint.
[0009] In an optional embodiment, the filler comprises, by weight, 0.05%-0.2% C, 0.1%-0.7% Cu, 0.2%-1% Cr, 0.5%-1.5% Mo, and 2.0%-4.5% Ni. The formula is suitable for welding base materials with a strength of ≤1600MPa.
[0010] In an optional embodiment, in the filler, by weight, C accounts for 0.2%-0.35%, Cu accounts for 0.7%-1.3%, Cr accounts for 1.0%-1.8%, Mo accounts for 1.5%-2.5%, and Ni accounts for 4.5%-7%. The formula is suitable for welding base materials with a strength of ≤1900MPa.
[0011] In an optional embodiment, in the filler, by weight, C accounts for 0.35%-0.5%, Cu accounts for 1.3%-2.0%, Cr accounts for 1.8%-2.5%, Mo accounts for 2.5%-3.5%, and Ni accounts for 7%-10%. The formula is suitable for welding base materials with a strength of ≤2200MPa.
[0012] According to another aspect of an embodiment of the present invention, a high-strength steel laser welded joint is provided, which is formed by laser filler welding using a hot-formed steel plate having at least one surface with pure aluminum or an aluminum-based coating, wherein the welded joint is welded using any of the aforementioned laser welding fillers, and in the solidification structure of the laser filler weld, in any region, by weight ratio, it includes 0.02%-0.25% Cu, 0.1%-1.2% Cr, 0.1%-1.2% Mo, 0.4%-3% Ni, 0.3%-0.8% Si, and 0.8%-1.8% Mn. The weld region of the joint has a uniform structure, and analysis using an electron microscope or X-ray diffraction shows that the solidification structure shows good uniformity everywhere, and there is no flake ferrite or brittle phase formed by element segregation.
[0013] Furthermore, in the solidified structure of the high-strength steel laser welded joint, in any region, the element content satisfies 2%≤Cu+Cr+Mo+Ni+Si+Mn≤6% by weight. Too low alloy component content in the solidified structure of the joint will lead to insufficient strength, while too high alloy component content will easily lead to segregation, which will also have an adverse effect on strength.
[0014] According to another aspect of the embodiment of the present invention, a high-strength steel laser welding method is provided, wherein laser filler welding is used to weld a hot-formed steel plate having pure aluminum or aluminum-based coating on at least one surface, wherein the hot-formed steel has a base material strength of ≤1600MPa after hot stamping, and a filler containing 0.05%-0.2% C, 0.1%-0.7% Cu, 0.2%-1% Cr, 0.5%-1.5% Mo, and 2.0%-4.5% Ni is used for welding. The strength and plasticity of the welded joint provided by the welding method after hot stamping are both above 90% of the base material.
[0015] According to another aspect of the embodiment of the present invention, a high-strength steel laser welding method is provided, wherein laser filler welding is used to weld a hot-formed steel plate having pure aluminum or aluminum-based coating on at least one surface, wherein the hot-formed steel has a base material strength of 1600MPa-1900MPa after hot stamping, and a filler containing 0.2%-0.35% C, 0.7%-1.3% Cu, 1.0%-1.8% Cr, 1.5%-2.5% Mo, and 4.5%-7% Ni is used for welding. The strength and plasticity of the welded joint provided by the welding method after hot stamping are both above 90% of the base material.
[0016] According to another aspect of the embodiment of the present invention, a high-strength steel laser welding method is provided, wherein laser filler welding is used to weld a hot-formed steel plate having pure aluminum or aluminum-based coating on at least one surface, wherein the hot-formed steel has a base material strength of 1900MPa-2200MPa after hot stamping, and a filler containing 0.35%-0.5% C, 1.3%-2.0% Cu, 1.8%-2.5% Cr, 2.5%-3.5% Mo, and 7%-10% Ni is used for welding. The strength and plasticity of the welded joint provided by the welding method after hot stamping are both above 90% of the base material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a distribution diagram of Cr elements in a weld cross section under an electron microscope in one embodiment;
[0018] Figure 2 This is a Ni element distribution diagram of a weld cross section under an electron microscope in one embodiment;
[0019] Figure 3 Schematic diagram of phase composition at different temperatures in the weld area in one embodiment;
[0020] Figure 4 A pair of proportional distribution diagrams of Cr elements in the weld section under an electron microscope;
[0021] Figure 5 A pair of proportional distribution diagrams of Ni elements in the weld cross section under an electron microscope;
[0022] Figure 6 A schematic diagram of the phase composition at different temperatures in the weld area in a pair of ratios;
[0023] Figure 7a is a tensile test result of a welded joint in an embodiment;
[0024] Figure 7b This is the tensile test result of the welded joint in another comparative example.
[0025] The purpose of the above drawings is to describe the present invention in detail so that those skilled in the art can understand the technical concept of the present invention, but it is not intended to limit the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0027] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The phrase appearing in various locations in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive independent or alternative embodiments. Those skilled in the art should be able to understand that the embodiments herein may be combined with other embodiments without causing structural conflicts.
[0028] The processing of hot-formed steel parts requires heating the base material to 880℃-950℃ and keeping it warm for 3-6 minutes, then forming it under the mold and cooling it quickly so that the matrix forms a structure composed entirely of martensite, thereby increasing the strength from 500MPa level to 1500MPa or even higher, while having an elongation of more than 5%. When hot-formed steel is used as a high-strength structural material for production and manufacturing, the base material that has not been hot-stamped is first cut, welded, and processed for preliminary forming, and then hot-stamped to obtain a finished workpiece with a structure that meets the application requirements. During the welding process, the aluminum-containing coating on the surface of the hot-formed steel will enter the weld structure and mix with the molten hot-formed steel, so that the weld solidification structure of the joint after hot stamping is no longer composed of complete martensite, but often contains ferrite and intermetallic compounds with low strength or plasticity. The strength and plasticity of the weld joint are severely weakened. The mechanical properties of the weld joint area are even less than 70% of the parent material. When failure occurs, the fracture usually occurs in the weld area, which often cannot meet the design requirements and restricts the application of hot-formed steel in the industrial field.
[0029] In order to solve the above problems, an embodiment of one aspect of the present invention provides a laser welding filler, the composition of the filler, the strength of the welding base material and the welding parameters are shown in Table 1, wherein the surface of the base material is coated with an aluminum-silicon coating. For welding base materials with higher strength, the proportion of alloy components in the welding filler used is also higher. On the one hand, the alloy components in the filler can stabilize the austenite in the weld structure to offset the ferrite inclination caused by the Al element, and on the other hand, improve the strength and toughness by increasing the alloying degree of the weld structure, and avoid the segregation of a single element by reasonably controlling the content of different elements. Among them, Cu can replace Ni to a certain extent, and Mo can replace Cr to a certain extent, so as to achieve the effect of improving the mechanical properties of the joint. Because Ni and Cr are both prone to segregation in the weld solidification structure when the content is high, causing the mechanical properties to decline, and Cr will further combine with C to generate harmful carbides to cause local carbon deficiency, reducing the overall strength of the weld structure. In order to further improve the joint strength, the inevitable impurity components in the filler, especially S and P, should be further controlled in terms of weight ratio, S≤0.01%, P≤0.03%. According to the components provided in Table 1, different raw materials are melted and mixed to form welding wires with a diameter of 0.8mm-1.6mm for welding, and then the welded parts are hot stamped and tensile specimens are prepared. The strength and plasticity of the obtained joint tensile specimens in the uniaxial tensile test are more than 90% of the mechanical properties of the parent material after hot stamping. Among them, taking the welding wire diameter of 1.0mm as an example, the matching relationship between the welding speed and the wire feeding speed is: when the plate thickness is 1.0mm, the welding speed is 2.5-3.0 times the wire feeding speed; when the plate thickness is 1.5mm, the welding speed is 1.5-2.0 times the wire feeding speed; when the plate thickness is 2.0mm, the welding speed is 0.8-1.3 times the wire feeding speed. Under the same wire feeding speed, the thicker the plate, the smaller the welding speed to increase the filling amount. The filler provided in Table 1 matches the hardness of the parent material, and the hardness, strength and plasticity of the weld structure after overall hot stamping are close to those of the parent material. Fillers suitable for higher-strength base materials can also be used for welding lower-strength base materials, but the plasticity of the weld structure will decrease after hot stamping; and using fillers used for lower-strength base materials for welding higher-strength base materials will lead to a decrease in the mechanical properties of the joint.
[0030]
[0031] Table 1 Filler solder composition and filling amount range
[0032] In a preferred embodiment, the filler also contains 0.5%-3% Si and 1.0%-5.0% Mn by weight. Among them, Si can improve the fluidity of the filler, promote the full flow of the filler during welding, make the alloy components fully and evenly diffuse, and avoid the aggregation of the Al-containing coating; the addition of Mn can reduce the amount of C and reduce the formation of harmful carbides. In one embodiment, a steel plate with an aluminum-silicon coating with a strength of 1500MPa after hot stamping is used as the base material, and a welding wire containing 0.1% C, 0.2% Cu, 0.5% Cr, 1.0% Mo, and 4.0% Ni by weight is used as a filler for laser filler welding and hot stamping. The tensile strength of the obtained joint sample is about 1360MPa; in a preferred embodiment, after adding 0.8% Si and 1.5% Mn to the welding wire, the tensile strength of the sample is increased to more than 1400MPa. In another preferred embodiment, a steel plate with an aluminum-silicon coating having a strength of 2000 MPa after hot stamping is used as the base material, and a welding wire containing 0.35% C, 1.0% Cu, 1.2% Cr, 3.0% Mo, 9.0% Ni, 1.2% Si and 2.4% Mn by weight is used as a filler for laser filler welding and hot stamping, and the resulting joint sample has a tensile strength of more than 1900 MPa.
[0033] In a further preferred embodiment, the filler also contains 0.1%-1% Ti by weight. The addition of Ti can promote the grain refinement of the solidification structure. At the same time, Ti combined with part of C can play a pinning role, further improving the mechanical properties of the joint. In one embodiment, a steel plate with an aluminum-silicon coating with a strength of 1900MPa after hot stamping is used as the base material, and a welding wire containing 0.25% C, 0.5% Cu, 1.0% Cr, 2.0% Mo, 7.0% Ni, 1.2% Si and 1.8% Mn by weight is used as a filler for laser filler welding and hot stamping. The tensile strength of the obtained joint sample is 1720MPa; in a further preferred embodiment, after adding 0.5% Ti to the welding wire, the tensile strength of the sample is increased to more than 1800MPa.
[0034] Another embodiment of the present invention further provides a high-strength steel laser welding joint, which uses the high-strength steel laser welding filler in any of the aforementioned embodiments to perform laser filler welding on a hot-formed steel plate having pure aluminum or aluminum-based coating on at least one surface.
[0035] In one embodiment, a hot-formed steel with an aluminum-silicon coating on the surface having a tensile strength of 1500 MPa or less after hot stamping is used as a base material, and a welding wire containing 0.1% C, 0.5% Cu, 0.5% Cr, 1.0% Mo, 4.0% Ni, 0.8% Si and 1.5% Mn by weight, with the remainder being Fe, is used for laser welding, and the welded plate is hot stamped. The tensile strength of the welded joint is sampled and tested to be above 90% of the base material. Under a scanning electron microscope, the element solidification structure of the weld that melts and mixes the aluminum-silicon coating, the hot-formed steel matrix, and the filler welding wire during the laser welding process is detected by element detection. The element content is calculated by weight, and contains 0.07% Cu, 0.21% Cr, 0.14% Mo, 0.54% Ni, 0.54% Si, and 1.11% Mn, and the sum of the contents of the above elements is 2.87%.
[0036] In another embodiment, a hot-formed steel with an aluminum-silicon coating on the surface having a tensile strength of 1900 MPa after hot stamping is used as a base material, and a welding wire containing 0.25% C, 1.0% Cu, 1.5% Cr, 2.0% Mo, 6.0% Ni, 1.2% Si and 2.0% Mn by weight, with the remainder being Fe, is used for laser welding, and the welded plate is hot stamped. The tensile strength of the welded joint is more than 90% of the base material after sampling and testing. Under a scanning electron microscope, the solidified structure of the aluminum-silicon coating, the hot-formed steel matrix and the filler welding wire melted and mixed during the laser welding process is subjected to element detection. The element content is calculated by weight, and contains 0.14% Cu, 0.38% Cr, 0.27% Mo, 0.82% Ni, 0.60% Si, 1.57% Mn, and the sum of the contents of the above elements is 4.06%.
[0037] In another embodiment, a hot-formed steel with an aluminum-silicon coating on the surface having a tensile strength of 2200 MPa after hot stamping is used as a base material, and a welding wire with a weight ratio of 0.38% C, 1.5% Cu, 2.0% Cr, 3.0% Mo, 9.0% Ni, 1.5% Si and 3.0% Mn, and the balance of Fe is used for laser welding, and the welded plate is hot stamped. The tensile strength of the welded joint is more than 90% of the base material after sampling and testing. The elements of the solidified area where the aluminum-silicon coating, the hot-formed steel matrix and the filler wire are melted and mixed during the laser welding process are detected. The element content is calculated by weight, and contains 0.2% Cu, 1.11% Cr, 0.41% Mo, 1.22% Ni, 0.62% Si, 1.66% Mn, and the sum of the contents of the above elements is 5.61%.
[0038] In a pair of proportions, a welding wire containing not more than 0.3% C, not more than 1.3% Si, 0.5%-7% Mn, 5%-22% Cr, 6%-20% Ni and not more than 0.4% Mo by weight is used as a filler for laser filler welding, and the tensile strength of the obtained joint is less than 1200MPa.
[0039] The energy spectrum analysis (Map Data5) of the welded joint section in one embodiment is performed, and the distribution of Cr and Ni is as follows: Figure 1 , Figure 2 As shown, Figure 1 The middle red represents the distribution of Cr elements. Figure 2 The green color in the middle represents the distribution of Ni elements. It can be seen that the content of Cr and Ni in the weld area is higher than that of the base material and is evenly distributed. The line scan results in Line Data5, Line Data6, and Line Data7 also show that the Cr and Ni elements are evenly distributed in the weld area. These alloy components can effectively play a strengthening role, making the joint show higher strength and plasticity. The energy spectrum analysis (Map Data14) of the welded joint section in the above comparative example shows that the distribution of Cr and Ni is as follows: Figure 3 , Figure 4 As shown, similarly Figure 3 The middle red represents the distribution of Cr elements. Figure 4 The middle green represents the distribution of Ni elements. It can be seen that the Cr and Ni elements are enriched in the weld area and the base material to form a relatively clear boundary, while in area 1, which is the edge area of the weld surface, Cr and Ni are obviously segregated. Line scanning of Line Data 12 further shows that the segregation of Cr and Ni elements occurs not only in area 1, but also in other locations in the weld, which leads to insufficient overall mechanical properties of the joint. Phase composition simulation calculations were performed on the embodiment and the comparative example, and the results are shown in Figure 1. Figure 3 and Figure 6 As shown, the horizontal axis is temperature (Temperature), and the vertical axis is the molar percentage (Mole) of different phases in the equilibrium state. It can be seen that the Fe element in the weld structure is mainly in the liquid phase (Liquid) above 1400°C, and after solidification it mainly exists in the form of austenite (Austenite), ferrite (Ferrite) and cementite (Cementite). During the hot stamping process, within the hot stamping temperature range, the overall structure is mainly austenite. If the weld structure is slowly cooled in an equilibrium process, it will be transformed into a ferrite-based structure at room temperature, and the strength is insufficient. Therefore, it needs to be quenched and cooled quickly to retain the austenite structure. The presence of Cr and Ni elements helps to enhance the stability of austenite. At the same time, some alloying elements in the weld structure will be in the form of M 23C6, M2 (C, N), etc. When the content of alloying elements such as Cr is too high, it will combine with C elements to form M 23 C6 carbide precipitates in the form of carbon. When such carbides are present in large quantities in the weld, they will cause local carbon depletion and softening of the weld structure, which will have an adverse effect on the strength and toughness of the joint. Figure 3 and Figure 6 By comparison, it can be seen that in the embodiment ( Figure 3 ) in the weld structure 23 The content of C6 carbide is significantly lower than that of the comparative example ( Figure 6 ). Combined Figure 4 The enrichment of Cr in region 1 shows that excessive M 23 C6 carbides, which in turn make the position of area 1 the weak link of the weld joint. This segregation occurs not only in area 1 but also in any area of the weld structure. It can be seen that excessive content of alloy components has an adverse effect on the joint strength after hot stamping. The inventor designed the welding wire composition through calculation and analysis, and controlled the content of Cr and Ni elements on the basis of maintaining the stabilizing effect of Cr and Ni elements on austenite, eliminating the M 23 The adverse effect of C6 carbides on welded joints is reduced, achieving the goal of improving joint strength, toughness and elongation.
[0040] In another embodiment, a hot-formed steel having an aluminum-silicon coating on the surface and a tensile strength of 1500 MPa or less after hot stamping is used as a base material, and a welding wire containing 0.05%-0.1% C, 0.2%-0.5% Cu, 0.4%-0.8% Cr, 0.5%-1.0% Mo, and 2.0%-4.5% Ni by weight is used as a filler for laser filler welding. After hot stamping, a standard tensile specimen is made for tensile testing. The results are as follows: Figure 7a As shown in the figure, the joint strength exceeds 1400MPa, and the final fracture occurs in the base metal area. In another comparative example, a welding wire containing 0.1%-0.4% C, 0.5%-0.2% Si, 1%-2.5% Mn, 1.0%-4.0% Ni and 0.5%-2% Mo+Cr is used as a filler for laser filler welding. After hot stamping, the joint is made into a standard tensile specimen for tensile testing. The results are shown in Figure 7b As shown in the figure, the fracture occurs in the weld area. It can be seen that too low a proportion of alloy components in the welding filler will also have an adverse effect on the mechanical properties of the welded joint after hot stamping, reducing the strength and plasticity of the joint.
[0041] The purpose of the above embodiments is to further explain the present invention in detail in conjunction with the accompanying drawings so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the claims of the present invention, the optimization or equivalent replacement of the components or methods involved, and the combination of implementation methods in different embodiments without conflict of principle, all fall within the protection scope of the present invention.
Claims
1. A high-strength steel laser welding filler, characterized in that: With Fe as the substrate, its components by weight include: 0.05%-0.5% C, 0.7%-2% Cu, 0.2%-2.5% Cr, 1.0%-3.5% Mo, 2%-10% Ni, and unavoidable impurities; The high-strength steel laser welding filler is used for welding high-strength steel with pure aluminum or aluminum-based coating.
2. The high-strength steel laser welding filler according to claim 1, characterized in that: It also includes 1.0%-5.0% Mn and 0.5%-3.0% Si.
3. The high-strength steel laser welding filler according to claim 2, characterized in that: It also includes 0.1%-1% Ti.
4. The high-strength steel laser welding filler according to any one of claims 1 to 3, characterized in that: By weight, C accounts for 0.2%-0.35%, Cu accounts for 0.7%-1.3%, Cr accounts for 1.0%-1.8%, Mo accounts for 1.5%-2.5%, and Ni accounts for 4.5%-7%.
5. The high-strength steel laser welding filler according to any one of claims 1 to 3, characterized in that: By weight, C accounts for 0.35%-0.5%, Cu accounts for 1.3%-2.0%, Cr accounts for 1.8%-2.5%, Mo accounts for 2.5%-3.5%, and Ni accounts for 7%-10%.
6. A high-strength steel laser welded joint, formed by laser filler welding of a hot-formed steel plate having at least one surface with pure aluminum or aluminum-based coating, characterized in that: The high-strength steel laser welding filler as described in any one of claims 1 to 5 is used, and in any area in the solidification structure of the laser filler weld, by weight ratio, it includes 0.02%-0.25% Cu, 0.1%-1.2% Cr, 0.1%-1.2% Mo, 0.4%-3% Ni, 0.3%-0.8% Si, and 0.8%-1.8% Mn.
7. The high-strength steel laser welded joint according to claim 6, characterized in that: In the solidified structure of the weld, in any region, the element content satisfies 2%≤Cu+Cr+Mo+Ni+Si+Mn≤6% by weight.
8. A high-strength steel laser welding method, using laser filler welding to weld hot-formed steel plates having pure aluminum or aluminum-based coating on at least one surface, characterized in that: The base material strength of the hot-formed steel after hot stamping is 1600MPa-1900MPa, and the high-strength steel laser welding filler as claimed in claim 4 is used for welding.
9. A high-strength steel laser welding method, using laser filler welding to weld hot-formed steel plates having pure aluminum or aluminum-based coating on at least one surface, characterized in that: The base material strength of the hot-formed steel after hot stamping is 1900 MPa-2200 MPa, and the high-strength steel laser welding filler as claimed in claim 5 is used for welding.
Citation Information
Patent Citations
Method for fillet arc welding high-strength thin steel sheets
CN102548703A
High strength and toughness submerged arc welding wire of high-strength steel for ocean platform and weld metal prepared through welding wire
CN106001990A
Steel differential strength welding part with aluminum or aluminum alloy plating and manufacturing method of steel differential strength welding part
CN111215751A